Polyacrylonitrile ultrafiltration membrane as well as preparation method and application thereof
By using high molecular weight acrylonitrile copolymer and introducing hydrophilic groups, the problem of insufficient mechanical properties and hydrophilicity of polyacrylonitrile ultrafiltration membranes is solved, and high-efficiency filtration and long-life membrane performance are achieved.
Patent Information
- Application Number
- CN202510012114.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-06
- Publication Date
- 2025-03-04
AI Technical Summary
The existing polyacrylonitrile ultrafiltration membranes have poor mechanical properties and hydrophilicity during use, resulting in a decrease in filtration capacity and enhanced dirt adhesion, making it difficult to effectively remove dirt in the membrane.
By using high molecular weight acrylonitrile copolymers and introducing hydrophilic groups during their preparation, a polyacrylonitrile ultrafiltration membrane with high mechanical properties and high hydrophilicity is constructed. This method simplifies the preparation process without subsequent surface treatment.
The polyacrylonitrile ultrafiltration membrane has excellent mechanical strength and hydrophilicity, improved filtration performance and anti-fouling performance, extended the service life of the membrane, and reduced production costs.
Smart Images

Figure CN119549000A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of membrane materials, and in particular relates to a polyacrylonitrile ultrafiltration membrane and a preparation method and application thereof. Background Art
[0002] In industrial processes, oil-water emulsions are formed as final products or waste streams, and ultrafiltration membranes are the most economical way to treat oily wastewater. Due to its unique properties, ultrafiltration membranes can remove small particles in oil-water emulsions very well, but they require a certain driving force during use, and as the use time increases, the dirt in the membrane will also increase, resulting in a decrease in its filtration capacity.
[0003] Polyacrylonitrile (PAN) has the advantages of low material cost and good physical and chemical properties. It is a commonly used polymer for ultrafiltration membranes for wastewater treatment. There are also many studies on the modification of polyacrylonitrile membranes, but they are all through surface grafting, modification, addition of additives or post-treatment methods, and their mechanical properties and hydrophilicity are still poor. Summary of the invention
[0004] The object of the present invention is to provide a polyacrylonitrile ultrafiltration membrane and a preparation method and application thereof. The polyacrylonitrile ultrafiltration membrane provided by the present invention has excellent mechanical strength and hydrophilicity.
[0005] In order to achieve the above object, the present invention provides the following technical solutions:
[0006] The present invention provides a polyacrylonitrile ultrafiltration membrane, the chemical composition of which includes an acrylonitrile copolymer, wherein the acrylonitrile copolymer is a copolymer containing an unsaturated bond monomer and an acrylonitrile monomer, and the viscosity average molecular weight of the acrylonitrile copolymer is 2×10 4 ~1.5×10 6 .
[0007] Preferably, the acrylonitrile copolymer includes one or more of methyl acrylate-acrylonitrile copolymer, itaconic acid-acrylonitrile copolymer, acrylamide-acrylonitrile copolymer and propanesulfonic acid-acrylonitrile copolymer.
[0008] Preferably, the viscosity average molecular weight of the acrylonitrile copolymer is 2×10 5 ~1×10 6 .
[0009] Preferably, the polyacrylonitrile ultrafiltration membrane has a thickness of 0.5 to 500 μm.
[0010] The present invention also provides a method for preparing the polyacrylonitrile ultrafiltration membrane described in the above scheme, comprising the following steps:
[0011] The acrylonitrile copolymer, the porogen and the good solvent are mixed and then formed into a film on a substrate to obtain the polyacrylonitrile ultrafiltration membrane.
[0012] Preferably, the preparation method of the acrylonitrile copolymer is an aqueous phase precipitation method; the aqueous phase precipitation method comprises the following steps: mixing acrylonitrile monomer, unsaturated bond-containing monomer, initiator and water for free radical copolymerization.
[0013] Preferably, the unsaturated bond-containing monomer includes one or more of unsaturated acid monomers, unsaturated acid ester monomers, ammonium salts of unsaturated acids and unsaturated amide monomers.
[0014] Preferably, the temperature of the free radical copolymerization is 60-70° C., and the heat preservation polymerization time is 1-3 hours.
[0015] Preferably, the mass ratio of the porogen to the good solvent is no more than 3:100; and the mass ratio of the acrylonitrile copolymer to the good solvent is 1 to 10:100.
[0016] The present invention also provides the use of the polyacrylonitrile ultrafiltration membrane described in the above scheme or the polyacrylonitrile ultrafiltration membrane obtained by the preparation method described in the above scheme in water treatment.
[0017] The present invention provides a polyacrylonitrile ultrafiltration membrane. The present invention uses an ultrahigh molecular weight polyacrylonitrile copolymer and utilizes its high molecular weight characteristics to make the interaction between molecular chains and chemical bonds stronger, so that the molecular chains are not easy to slip, and then the tensile strength of the ultrafiltration membrane is significantly enhanced. The present invention introduces a hydrophilic group when preparing ultrahigh molecular weight polyacrylonitrile, so as to fundamentally improve the hydrophilicity and flexibility of the ultrafiltration membrane. The improvement of the hydrophilicity of the ultrafiltration membrane will improve the anti-fouling performance of the ultrafiltration membrane. Since the hydrophilic surface weakens the adhesion between the dirt and the ultrafiltration membrane, it is easier to remove the dirt in the ultrafiltration membrane after cleaning the ultrafiltration membrane. The present invention constructs a polyacrylonitrile ultrafiltration membrane with high mechanical properties and high hydrophilicity based on the flexibility of the polyacrylonitrile chain, the hydrophilicity of the group and the molecular weight distribution, taking into account its retention rate and water flux, extending the service life of the polyacrylonitrile ultrafiltration membrane, and the pore size is easy to control and the cost is low.
[0018] The present invention also provides a method for preparing the polyacrylonitrile ultrafiltration membrane described in the above scheme. The membrane preparation method provided by the present invention introduces hydrophilic groups during polymerization, does not require subsequent surface treatment (such as surface grafting of hydrophilic groups, surface alkaline hydrolysis, and surface cross-linking of various hydrophilic substances), has simple steps, and is easy to operate.
[0019] The present invention also provides the use of the polyacrylonitrile ultrafiltration membrane described in the above scheme or the polyacrylonitrile ultrafiltration membrane obtained by the preparation method described in the above scheme in water treatment. The polyacrylonitrile ultrafiltration membrane provided by the present invention has high strength, makes the polyacrylonitrile ultrafiltration membrane easy to operate, has good hydrophilicity, requires less raw materials, is conducive to reducing costs and saving resources. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0021] Figure 1 This is an electron microscope image (50 μm) of the polyacrylonitrile ultrafiltration membrane prepared in Example 1 of the present invention;
[0022] Figure 2 This is an electron microscope image (5 μm) of the polyacrylonitrile ultrafiltration membrane prepared in Example 1 of the present invention;
[0023] Figure 3 This is an electron microscope image (2 μm) of the polyacrylonitrile ultrafiltration membrane prepared in Example 1 of the present invention;
[0024] Figure 4 This is an electron microscope image (1 μm) of the polyacrylonitrile ultrafiltration membrane prepared in Example 1 of the present invention. DETAILED DESCRIPTION
[0025] The present invention provides a polyacrylonitrile ultrafiltration membrane, the chemical composition of which includes an acrylonitrile copolymer, wherein the acrylonitrile copolymer is a copolymer containing an unsaturated bond monomer and an acrylonitrile monomer, and the viscosity average molecular weight of the acrylonitrile copolymer is 2×10 4 ~1.5×10 6 .
[0026] In the present invention, the acrylonitrile copolymer preferably includes one or more of methyl acrylate-acrylonitrile copolymer, itaconic acid-acrylonitrile copolymer, acrylamide-acrylonitrile copolymer and propanesulfonic acid-acrylonitrile copolymer.
[0027] In the present invention, the viscosity average molecular weight of the acrylonitrile copolymer is 2×10 4 ~1.5×10 6 , specifically 2×10 4 , 5×10 4 , 8×10 4 , 1×10 5 , 2×10 5 , 5×10 5 ,7×10 5 , 1×10 6 , 1.2×10 6 or 1.5 × 10 6 .
[0028] In the present invention, the thickness of the polyacrylonitrile ultrafiltration membrane is preferably 0.5 to 500 μm, specifically 0.5 μm, 1 μm, 10 μm, 50 μm, 100 μm, 150 μm, 200 μm, 250 μm, 300 μm, 400 μm or 500 μm.
[0029] The polyacrylonitrile ultrafiltration membrane provided by the present invention has good mechanical properties, good hydrophilicity, high water flux, long service life, and can maintain 40L / (m 2 h), which promotes the application of polyacrylonitrile ultrafiltration membrane in water treatment.
[0030] The present invention also provides a method for preparing the polyacrylonitrile ultrafiltration membrane described in the above scheme, comprising the following steps:
[0031] The acrylonitrile copolymer, the porogen and the good solvent are mixed (referred to as the first mixing) and then formed into a film on a substrate to obtain the polyacrylonitrile ultrafiltration membrane.
[0032] In the present invention, the preparation method of the acrylonitrile copolymer is preferably an aqueous phase precipitation method; the aqueous phase precipitation method preferably comprises the following steps: mixing acrylonitrile monomer, unsaturated bond-containing monomer, initiator and water for free radical copolymerization.
[0033] In the present invention, the unsaturated bond-containing monomer preferably includes one or more of unsaturated acid monomers, unsaturated acid ester monomers, ammonium salts of unsaturated acids and unsaturated amide monomers; the unsaturated acid monomers preferably include one or both of itaconic acid and propanesulfonic acid; the unsaturated acid ester monomers are preferably methyl acrylate; the ammonium salt of unsaturated acids preferably includes ammonium itaconate; and the unsaturated amide monomers are preferably acrylamide.
[0034] In the present invention, the mass ratio of the unsaturated bond-containing monomer to the acrylonitrile monomer is preferably 1-5:1-35, specifically 1:1, 1:5, 1:10, 1:20, 1:30, 1:35, 2:1, 2:5, 2:10, 2:20, 2:30, 2:35, 3:1, 3:5, 3:10, 3:20, 3:30, 3:35, 4:1, 4.5:1 , 5:1, 4:3, 4.5:3, 5:3, 4:8, 4.5:8, 5:8, 4:12, 4.5:12, 5:12, 4:18, 4.5:18, 5:18, 4:22, 4.5:22, 5:22, 4:27, 4.5:27, 5:27, 4:32, 4.5:32, 5:32, 4:35, 4.5:35, or 5:35.
[0035] In the present invention, the initiator is preferably a redox initiator; the redox initiator preferably includes one or more of ammonium sulfite and ammonium persulfate; the ammonium sulfite is preferably ammonium sulfite monohydrate; the ratio of the mass of the initiator to the total mass of the acrylonitrile monomer and the unsaturated bond-containing monomer is preferably 0.001-0.3:5-40, specifically 0.001:5, 0.005:5, 0.01:5, 0.05:5, 0.1:5, 0.2:5, 0.3:5, 0.001:15, 0.005:15, 0.01:15 , 0.05:15, 0.1:15, 0.2:15, 0.3:15, 0.001:25, 0.005:25, 0.01:25, 0.05:25, 0.1:25, 0.2:25, 0.3:25, 0.001:35, 0.005:35, 0.01:35, 0.05:35, 0.1:35, 0.2:35, 0.3:35, 0.001:40, 0.005:40, 0.01:40, 0.05:40, 0.1:40, 0.2:40, or 0.3:40.
[0036] In the present invention, the water is preferably deionized water; the mass ratio of the unsaturated bond-containing monomer to water is preferably 1-30:70-90, and specifically can be 1:70, 5:70, 10:70, 15:70, 20:70, 25:70, 30:70, 1:75, 5:75, 10:75, 15:75, 20:75, 25:75, 30:75, 1:80, 5:80, 10:80, 15:80, 20:80, 25:80, 30:80, 1:85, 5:85, 10:85, 15:85, 20:85, 25:85, 30:85, 1:90, 5:90, 10:90, 15:90, 20:90, 25:90 or 30:90.
[0037] In the present invention, the temperature of the free radical copolymerization is preferably 60-70°C, specifically 60°C, 62°C, 64°C, 66°C, 68°C or 70°C, and the heat preservation polymerization time is preferably 1-3h, specifically 2h.
[0038] In the present invention, after the free radical copolymerization, the obtained product is preferably dried after solid-liquid separation; the solid-liquid separation is preferably carried out by suction filtration; the solid-liquid separation is preferably carried out under water washing conditions; and the drying is preferably oven drying.
[0039] In the present invention, the porogen preferably includes one or more of polyvinyl pyrrolidone, polyvinyl alcohol and polyethylene glycol; the polyethylene glycol is preferably PEG4000.
[0040] In the present invention, the mass ratio of the porogen to the good solvent is preferably no more than 3:100, and can be specifically 3:100, 2.8:100, 2.5:100, 2.3:100, 2:100, 1.5:100, 1:100, 0.8:100, 0.5:100 or 0.1:100. The present invention changes the phase separation result by adding additives and introducing different groups, so as to realize easy regulation of the membrane pore size.
[0041] In the present invention, the good solvent preferably includes one or more of an amide solvent, an alkane solvent and a sulfoxide solvent; the amide solvent preferably includes one or both of N,N-dimethylacetamide (DMAC) and dimethylformamide (DMF); the alkane solvent is preferably N,N-dimethylpyrrolidone (NMP); and the sulfoxide solvent is preferably dimethyl sulfoxide (DMSO).
[0042] In the present invention, the mass ratio of the acrylonitrile copolymer to the good solvent is preferably 1 to 10:100, specifically 1:100, 2:100, 3:100, 4:100, 4.5:100, 5:100, 5.5:100, 6:100, 7:100, 8:100, 9:100 or 10:100.
[0043] In the present invention, the first mixed raw material preferably also includes a hydrophilic additive; the hydrophilic additive is preferably silicon dioxide (SiO2). The present invention improves the hydrophilicity and strength of the polyacrylonitrile ultrafiltration membrane by adding the hydrophilic additive.
[0044] In the present invention, the mass ratio of the acrylonitrile copolymer to the hydrophilic additive is preferably 90-100:10-0.001, specifically 100:0.001, 100:0.005, 100:0.01, 100:0.05, 100:0.1, 100:0.3, 100:0.5, 100:1, 100:2, 100:3, 100:5, 100:7, 100:10, 95:0.001, 95: 0.005, 95:0.01, 95:0.05, 95:0.1, 95:0.3, 95:0.5, 95:1, 95:2, 95:3, 95:5, 95:7, 95:10, 90:0.001, 90:0.005, 90:0.01, 90:0.05, 90:0.1, 90:0.3, 90:0.5, 90:1, 90:2, 90:3, 90:5, 90:7 or 90:10.
[0045] In the present invention, the first mixing is preferably stirring mixing; the rotation speed of the stirring mixing is preferably 200-500rpm, specifically 200rpm, 300rpm, 400rpm or 500rpm, the temperature is preferably 70-90°C, specifically 70°C, 75°C, 80°C, 85°C or 90°C, and the mixing time is preferably 2-3.5h, specifically 2h, 2.4h, 2.7h, 3h, 3.2h or 3.5h.
[0046] In the present invention, after the first mixing, the obtained mixture is preferably allowed to stand; the standing temperature is preferably room temperature, and the standing time is preferably 5 to 10 hours, specifically 5 hours, 6 hours, 7 hours, 8 hours, 9 hours or 10 hours. The present invention degasses the mixture by standing to obtain a casting solution.
[0047] In the present invention, the film forming is preferably performed by coating the casting solution on the substrate by blade and then forming the film by phase separation in a coagulation bath.
[0048] In the present invention, the substrate is preferably a glass plate.
[0049] In the present invention, the coating equipment is preferably a scraper; the coating thickness is preferably 0.5 to 500 μm, specifically 0.5 μm, 1 μm, 5 μm, 10 μm, 20 μm, 50 μm, 100 μm, 150 μm, 200 μm, 300 μm, 400 μm or 500 μm.
[0050] In the present invention, the coagulation bath is preferably a non-solvent coagulation bath; the non-solvent coagulation bath preferably includes one or more of water, alcohol and ketone; the water is preferably deionized water; the alcohol preferably includes one or more of methanol, ethanol and ethylene glycol; the ketone is preferably acetone.
[0051] In the present invention, the temperature of the coagulation bath is preferably 0-60°C, specifically 0°C, 5°C, 10°C, 15°C, 20°C, 25°C, 30°C, 35°C, 40°C, 50°C or 60°C, and the insulation time is preferably not more than 5 min, specifically 5 min, 4 min, 3 min, 2 min or 1 min.
[0052] The present invention also provides the use of the polyacrylonitrile ultrafiltration membrane described in the above scheme or the polyacrylonitrile ultrafiltration membrane obtained by the preparation method described in the above scheme in water treatment.
[0053] The polyacrylonitrile ultrafiltration membrane provided by the invention has high strength, and is easy to operate. It has good hydrophilicity, requires less raw materials, and is beneficial to reducing costs and saving resources.
[0054] In order to further illustrate the present invention, the scheme of the present invention is described in detail below in conjunction with the accompanying drawings and embodiments, but they should not be understood as limiting the protection scope of the present invention.
[0055] The present invention and comparative examples use water-in-oil emulsion as the filtration stock solution for characterization, n-hexadecane as the oil phase, sodium lauryl sulfate as the emulsifier, water as the aqueous phase, the volume ratio of n-hexadecane to water is 1:99, the mass fraction of the emulsifier to the oil is 0.5wt%, and the water-in-oil emulsion is magnetically stirred for 2h after ultrasonic treatment, and the water-in-oil emulsion is stable within 1 month. The changes of the water-in-oil emulsion after filtration by the ultrafiltration membrane are used to characterize the filtration capacity of the ultrafiltration membrane, such as the retention rate and the flux recovery rate.
[0056] Comparative Example 1
[0057] (1) Preparation of methyl acrylate-acrylonitrile copolymer
[0058] 0.5 g of methyl acrylate and 49.5 g of acrylonitrile were added to acidified hot water (65°C, pH 3.01), and then a redox initiator (0.1265 g of ammonium sulfite monohydrate and 0.25 g of ammonium persulfate) was added. Free radical copolymerization was carried out at 65°C for 2 hours, and the material was filtered out. During the filtration process, it was rinsed with deionized water for 6 times, and then dried at 60°C for 48 hours to obtain a methyl acrylate-acrylonitrile copolymer.
[0059] (2) Preparation of casting solution
[0060] Using DMSO as solvent, add the copolymer and DMSO into a three-necked flask, the copolymer concentration is 5wt%, and dissolve at 75°C and 300rpm for 3h. After uniform dissolution, stand at room temperature for 10h to degas, and obtain a casting solution.
[0061] (3) Film formation
[0062] The casting solution was poured onto a glass plate, and a uniform film with a thickness of 200 μm was scraped out using a scraping knife, and then placed in a 25° C. deionized water coagulation bath for phase separation and membrane formation to obtain a polyacrylonitrile ultrafiltration membrane.
[0063] (4) Testing
[0064] The oil-in-water emulsion was used as the filtration stock solution, and a flat membrane ultrafiltration device was used to perform a filtration test on a polyacrylonitrile ultrafiltration membrane.
[0065] Example 1
[0066] (1) Preparation of methyl acrylate-acrylonitrile copolymer
[0067] 0.5 g of methyl acrylate and 49.5 g of acrylonitrile were added to acidified hot water (65°C, pH 3.01), and then a redox initiator (0.1265 g of ammonium sulfite monohydrate, 0.25 g of ammonium persulfate) was added. The free radical copolymerization reaction was carried out at 65°C for 2 h, and the material was filtered out. During the filtration process, it was rinsed with deionized water for 6 times, and then dried at 60°C for 48 h to obtain a methyl acrylate-acrylonitrile copolymer with a viscosity-average molecular weight of 4×10 4 .
[0068] (2) Preparation of casting solution
[0069] Using DMSO as solvent, add copolymer, DMSO and porogen (PEG4000) into a three-necked flask, the concentration of copolymer is 5wt%, the concentration of porogen is 0.5wt%, dissolve at 75℃ and 300rpm for 3h, after uniform dissolution, stand at room temperature for 10h to degas, and obtain casting solution.
[0070] (3) Film formation
[0071] The casting solution was poured onto a glass plate, and a uniform film with a thickness of 200 μm was scraped out using a scraping knife, and then placed in a 25° C. deionized water coagulation bath for phase separation and membrane formation to obtain a polyacrylonitrile ultrafiltration membrane.
[0072] (4) Testing
[0073] The oil-in-water emulsion was used as the filtration stock solution, and a flat membrane ultrafiltration device was used to perform a filtration test on a polyacrylonitrile ultrafiltration membrane.
[0074] Example 2
[0075] (1) Preparation of methyl acrylate-acrylonitrile copolymer
[0076] 0.5 g of methyl acrylate and 49.5 g of acrylonitrile were added to acidified hot water (65°C, pH 3.01), and then a redox initiator (0.1265 g of ammonium sulfite monohydrate, 0.25 g of ammonium persulfate) was added. The free radical copolymerization reaction was carried out at 65°C for 2 h, and the material was filtered out. During the filtration process, it was rinsed with deionized water for 6 times, and then dried at 60°C for 48 h to obtain a methyl acrylate-acrylonitrile copolymer with a viscosity-average molecular weight of 4×10 4 .
[0077] (2) Preparation of casting solution
[0078] Using DMSO as solvent, add copolymer, SiO2, DMSO and porogen (PEG4000) into a three-necked flask, the concentration of copolymer is 5wt%, the concentration of porogen is 0.5wt%, the concentration of copolymer is 5wt%, the concentration of porogen is 0.5wt%, the mass ratio of SiO2 to copolymer is 0.3:100, dissolve at 75℃ and 300rpm for 3h, after uniform dissolution, stand at room temperature for 10h to degas, and obtain casting solution.
[0079] (3) Film formation
[0080] The casting solution was poured onto a glass plate, and a uniform film with a thickness of 200 μm was scraped out using a scraping knife, and then placed in a 25° C. deionized water coagulation bath for phase separation and membrane formation to obtain a polyacrylonitrile ultrafiltration membrane.
[0081] (4) Testing
[0082] The oil-in-water emulsion was used as the filtration stock solution, and a flat membrane ultrafiltration device was used to perform a filtration test on a polyacrylonitrile ultrafiltration membrane.
[0083] Example 3
[0084] (1) Preparation of methyl acrylate-acrylonitrile copolymer
[0085] 0.5 g of methyl acrylate and 49.5 g of acrylonitrile were added to acidified hot water (65°C, pH 3.01), and then a redox initiator (0.1265 g of ammonium sulfite monohydrate, 0.25 g of ammonium persulfate) was added. The free radical copolymerization reaction was carried out at 65°C for 2 h, and the material was filtered out. During the filtration process, it was rinsed with deionized water for 6 times, and then dried at 60°C for 48 h to obtain a methyl acrylate-acrylonitrile copolymer with a viscosity-average molecular weight of 4×10 4 .
[0086] (2) Preparation of casting solution
[0087] Using DMSO as solvent, add copolymer, DMSO and porogen (PEG4000) into a three-necked flask, the concentration of copolymer is 5wt%, the concentration of porogen is 1.5wt%, and dissolve at 75℃, 300rpm for 3h. After uniform dissolution, stand at room temperature for 10h for degassing to obtain casting solution.
[0088] (3) Film formation
[0089] The casting solution was poured onto a glass plate, and a uniform film with a thickness of 200 μm was scraped out using a scraping knife, and then placed in a 35° C. methanol coagulation bath for phase separation and membrane formation to obtain a polyacrylonitrile ultrafiltration membrane.
[0090] (4) Testing
[0091] The oil-in-water emulsion was used as the filtration stock solution, and a flat membrane ultrafiltration device was used to perform a filtration test on a polyacrylonitrile ultrafiltration membrane.
[0092] Example 4
[0093] (1) Preparation of methyl acrylate-acrylonitrile copolymer
[0094] 0.5 g of methyl acrylate and 49.5 g of acrylonitrile were added to acidified hot water (65°C, pH 3.01), and then a redox initiator (0.1265 g of ammonium sulfite monohydrate, 0.25 g of ammonium persulfate) was added. The free radical copolymerization reaction was carried out at 65°C for 2 h, and the material was filtered out. During the filtration process, it was rinsed with deionized water for 6 times, and then dried at 60°C for 48 h to obtain a methyl acrylate-acrylonitrile copolymer with a viscosity-average molecular weight of 4×10 4 .
[0095] (2) Preparation of casting solution
[0096] Using DMSO as solvent, add copolymer, SiO2, DMSO and porogen (PEG4000) into a three-necked flask, the concentration of copolymer is 5wt%, the concentration of porogen is 1.5wt%, the mass ratio of SiO2 to copolymer is 0.3:100, dissolve at 75℃, 300rpm for 3h, after uniform dissolution, stand at room temperature for 10h to degas, and obtain casting solution.
[0097] (3) Film formation
[0098] The casting solution was poured onto a glass plate, and a uniform film with a thickness of 200 μm was scraped out using a scraping knife, and then placed in a 35° C. methanol coagulation bath for phase separation and membrane formation to obtain a polyacrylonitrile ultrafiltration membrane.
[0099] (4) Testing
[0100] The oil-in-water emulsion was used as the filtration stock solution, and a flat membrane ultrafiltration device was used to perform a filtration test on a polyacrylonitrile ultrafiltration membrane.
[0101] Example 5
[0102] (1) Preparation of methyl acrylate-acrylonitrile copolymer
[0103] 0.75 g of methyl acrylate and 49.25 g of acrylonitrile were added to acidified hot water (65°C, pH 3.01), and then a redox initiator (0.1265 g of ammonium sulfite monohydrate, 0.25 g of ammonium persulfate) was added. The free radical copolymerization reaction was carried out at 65°C for 2 h, and the material was filtered out. During the filtration process, it was rinsed with deionized water for 6 times, and then dried at 60°C for 48 h to obtain a methyl acrylate-acrylonitrile copolymer with a viscosity-average molecular weight of 6×10 4 .
[0104] (2) Preparation of casting solution
[0105] Using DMSO as solvent, add copolymer, DMSO and porogen (PEG4000) into a three-necked flask, the concentration of copolymer is 5wt%, the concentration of porogen is 1.5wt%, dissolve at 75℃ and 300rpm for 3h, after uniform dissolution, stand at room temperature for 10h to degas, and obtain casting solution.
[0106] (3) Film formation
[0107] The casting solution was poured onto a glass plate, and a uniform film with a thickness of 200 μm was scraped out using a scraping knife, and then placed in a 25° C. methanol coagulation bath for phase separation and membrane formation to obtain a polyacrylonitrile ultrafiltration membrane.
[0108] (4) Testing
[0109] The oil-in-water emulsion was used as the filtration stock solution, and a flat membrane ultrafiltration device was used to perform a filtration test on a polyacrylonitrile ultrafiltration membrane.
[0110] Example 6
[0111] (1) Preparation of methyl acrylate-acrylonitrile copolymer
[0112] 0.75 g of methyl acrylate and 49.25 g of acrylonitrile were added to acidified hot water (65°C, pH 3.01), and then a redox initiator (0.1265 g of ammonium sulfite monohydrate, 0.25 g of ammonium persulfate) was added. The free radical copolymerization reaction was carried out at 65°C for 2 h, and the material was filtered out. During the filtration process, it was rinsed with deionized water for 6 times, and then dried at 60°C for 48 h to obtain a methyl acrylate-acrylonitrile copolymer with a viscosity-average molecular weight of 6×10 4 .
[0113] (2) Preparation of casting solution
[0114] Using DMSO as solvent, add copolymer, SiO2, DMSO and porogen (PEG4000) into a three-necked flask, the concentration of copolymer is 5wt%, the concentration of porogen is 1.5wt%, the mass ratio of SiO2 to copolymer is 0.3:100, dissolve at 75℃ and 300rpm for 3h, and after uniform dissolution, stand at room temperature for 10h to degas, and obtain the casting solution.
[0115] (3) Film formation
[0116] The casting solution was poured onto a glass plate, and a uniform film with a thickness of 200 μm was scraped out using a scraping knife, and then placed in a 25° C. methanol coagulation bath for phase separation and membrane formation to obtain a polyacrylonitrile ultrafiltration membrane.
[0117] (4) Testing
[0118] The oil-in-water emulsion was used as the filtration stock solution, and a flat membrane ultrafiltration device was used to perform a filtration test on a polyacrylonitrile ultrafiltration membrane.
[0119] Example 7
[0120] (1) Preparation of acrylic acid-acrylonitrile copolymer
[0121] 0.5 g of acrylic acid and 49.5 g of acrylonitrile were added to acidified hot water (65°C, pH 3.01), and then a redox initiator (0.1265 g of ammonium sulfite monohydrate and 0.25 g of ammonium persulfate) was added. The free radical copolymerization reaction was carried out at 65°C for 2 h, and the material was filtered out. During the filtration process, it was rinsed with deionized water for 6 times, and then dried at 60°C for 48 h to obtain a methyl acrylate-acrylonitrile copolymer with a viscosity-average molecular weight of 4×10 4 .
[0122] (2) Preparation of casting solution
[0123] Using DMSO as solvent, add copolymer, DMSO and porogen (PEG4000) into a three-necked flask, the concentration of copolymer is 5wt%, the concentration of porogen is 1.5wt%, dissolve at 75℃ and 300rpm for 3h, after uniform dissolution, stand at room temperature for 10h to degas, and obtain casting solution.
[0124] (3) Film formation
[0125] The casting solution was poured onto a glass plate, and a uniform film with a thickness of 200 μm was scraped out using a scraping knife, and then placed in a 25° C. ethanol coagulation bath for phase separation and membrane formation to obtain a polyacrylonitrile ultrafiltration membrane.
[0126] (4) Testing
[0127] The oil-in-water emulsion was used as the filtration stock solution, and a flat membrane ultrafiltration device was used to perform a filtration test on a polyacrylonitrile ultrafiltration membrane.
[0128] Example 8
[0129] (1) Preparation of acrylic acid-acrylonitrile copolymer
[0130] 0.5 g acrylic acid and 49.5 g acrylonitrile were added to acidified hot water (65°C, pH 3.01), and then a redox initiator (0.1265 g ammonium sulfite monohydrate, 0.25 g ammonium persulfate) was added. The free radical copolymerization reaction was carried out at 65°C for 2 h, and the material was filtered out. During the filtration process, it was rinsed with deionized water for 6 times, and then dried at 60°C for 48 h to obtain a methyl acrylate-acrylonitrile copolymer with a viscosity-average molecular weight of 4×10 4 .
[0131] (2) Preparation of casting solution
[0132] Using DMSO as solvent, add copolymer, SiO2, DMSO and porogen (PEG4000) into a three-necked flask, the concentration of copolymer is 5wt%, the concentration of porogen is 1.5wt%, the mass ratio of SiO2 to copolymer is 0.3:100, dissolve at 75℃ and 300rpm for 3h, and after uniform dissolution, stand at room temperature for 10h to degas, and obtain the casting solution.
[0133] (3) Film formation
[0134] The casting solution was poured onto a glass plate, and a uniform film with a thickness of 200 μm was scraped out using a scraping knife, and then placed in a 35° C. ethanol coagulation bath for phase separation and film formation to obtain a polyacrylonitrile ultrafiltration membrane.
[0135] (4) Testing
[0136] The oil-in-water emulsion was used as the filtration stock solution, and a flat membrane ultrafiltration device was used to perform a filtration test on a polyacrylonitrile ultrafiltration membrane.
[0137] Example 9
[0138] (1) Preparation of acrylic acid-acrylonitrile copolymer
[0139] 0.75 g of acrylic acid and 49.25 g of acrylonitrile were added to acidified hot water (65°C, pH 3.01), and then a redox initiator (0.1265 g of ammonium sulfite monohydrate, 0.25 g of ammonium persulfate) was added. The free radical copolymerization reaction was carried out at 65°C for 2 h, and the material was filtered out. During the filtration process, it was rinsed with deionized water for 6 times, and then dried at 60°C for 48 h to obtain a methyl acrylate-acrylonitrile copolymer with a viscosity-average molecular weight of 6×10 4 .
[0140] (2) Preparation of casting solution
[0141] Using DMSO as solvent, add copolymer, DMSO and porogen (PEG4000) into a three-necked flask, the concentration of copolymer is 5wt%, the concentration of porogen is 1.5wt%, dissolve at 75℃ and 300rpm for 3h, after uniform dissolution, stand at room temperature for 10h to degas, and obtain casting solution.
[0142] (3) Film formation
[0143] The casting solution was poured onto a glass plate, and a uniform film with a thickness of 200 μm was scraped out using a scraping knife, and then placed in a 25° C. ethanol coagulation bath for phase separation and membrane formation to obtain a polyacrylonitrile ultrafiltration membrane.
[0144] (4) Testing
[0145] The oil-in-water emulsion was used as the filtration stock solution, and a flat membrane ultrafiltration device was used to perform a filtration test on a polyacrylonitrile ultrafiltration membrane.
[0146] Example 10
[0147] (1) Preparation of acrylic acid-acrylonitrile copolymer
[0148] 0.75 g of acrylic acid and 49.25 g of acrylonitrile were added to acidified hot water (65°C, pH 3.01), and then a redox initiator (0.1265 g of ammonium sulfite monohydrate, 0.25 g of ammonium persulfate) was added. The free radical copolymerization reaction was carried out at 65°C for 2 h, and the material was filtered out. During the filtration process, it was rinsed with deionized water for 6 times, and then dried at 60°C for 48 h to obtain a methyl acrylate-acrylonitrile copolymer with a viscosity-average molecular weight of 6×10 4 .
[0149] (2) Preparation of casting solution
[0150] Using DMSO as solvent, add copolymer, SiO2, DMSO and porogen (PEG4000) into a three-necked flask, the concentration of copolymer is 5wt%, the concentration of porogen is 1.5wt%, the mass ratio of SiO2 to copolymer is 0.3:100, dissolve at 75℃ and 300rpm for 3h, and after uniform dissolution, stand at room temperature for 10h to degas, and obtain the casting solution.
[0151] (3) Film formation
[0152] The casting solution was poured onto a glass plate, and a uniform film with a thickness of 200 μm was scraped out using a scraping knife, and then placed in a 35° C. ethanol coagulation bath for phase separation and film formation to obtain a polyacrylonitrile ultrafiltration membrane.
[0153] (4) Testing
[0154] The oil-in-water emulsion was used as the filtration stock solution, and a flat membrane ultrafiltration device was used to perform a filtration test on a polyacrylonitrile ultrafiltration membrane.
[0155] Test Example 1
[0156] The polyacrylonitrile ultrafiltration membrane prepared in Example 1 of the present invention was analyzed by electron microscope. The results are as follows: Figures 1 to 4 As shown. Figures 1 to 4 It can be seen that the ultrafiltration membrane of the present invention has a distinct finger-like structure and a dense layer structure of 1 to 2 μm. There is another dense layer below the dense layer, and the surface pore size is 100 nm to 1 μm, which verifies that the ultrafiltration membrane of the present invention has structural factors of strong filtration capacity and high flux.
[0157] Test Example 2
[0158] The test results of Examples 1 to 10 of the present invention are shown in Table 1.
[0159] Table 1 Performance data of polyacrylonitrile ultrafiltration membranes of Examples 1 to 10
[0160]
[0161] It can be seen from Table 1 that the ultrafiltration membrane of the present invention can achieve 1400L / M without any surface treatment. 2 The water flux of the membrane is more than 10000 h, the flux recovery rate is more than 67%, the retention rate is 99.9%, and the oil concentration of the filtrate obtained by the test is below 8 ppm, indicating that the ultrafiltration membrane of the present invention has excellent water flux and retention flux, high retention rate, and can be reused.
[0162] Test Example 3
[0163] The mechanical properties of the polyacrylonitrile ultrafiltration membranes of Examples 4, 6 and 10 were tested in accordance with the GB / T1040.3-2006 standard. The results are shown in Table 2.
[0164] Table 2 Mechanical properties of polyacrylonitrile ultrafiltration membranes of Examples 4, 6 and 10
[0165] Maximum load / N Maximum stroke / mm Example 4 0.991 1.48 Example 6 2.29 1.24 Example 10 3.38 1.01
[0166] It can be seen from Table 2 that the ultrafiltration membrane provided by the present invention has excellent mechanical properties.
[0167] It can be seen from the above examples that the polyacrylonitrile ultrafiltration membrane provided by the present invention has high mechanical properties and high hydrophilicity, takes into account its retention rate and water flux, and prolongs the service life of the polyacrylonitrile ultrafiltration membrane.
[0168] Although the above embodiment describes the present invention in detail, it is only a part of the embodiments of the present invention, not all of the embodiments. Other embodiments can be obtained based on this embodiment without creativity, and these embodiments all fall within the protection scope of the present invention.
Claims
1. A polyacrylonitrile ultrafiltration membrane, characterized in that: The chemical composition includes an acrylonitrile copolymer, wherein the acrylonitrile copolymer is a copolymer containing an unsaturated bond monomer and an acrylonitrile monomer, and the viscosity average molecular weight of the acrylonitrile copolymer is 2×10 4 ~1.5×10 6 .
2. The polyacrylonitrile ultrafiltration membrane according to claim 1, characterized in that The acrylonitrile copolymer includes one or more of methyl acrylate-acrylonitrile copolymer, itaconic acid-acrylonitrile copolymer, acrylamide-acrylonitrile copolymer and propanesulfonic acid-acrylonitrile copolymer.
3. The polyacrylonitrile ultrafiltration membrane according to claim 1 or 2, characterized in that: The viscosity average molecular weight of the acrylonitrile copolymer is 2×10 5 ~1×10 6 .
4. The polyacrylonitrile ultrafiltration membrane according to claim 1, characterized in that The thickness of the polyacrylonitrile ultrafiltration membrane is 0.5-500 μm.
5. The method for preparing the polyacrylonitrile ultrafiltration membrane according to any one of claims 1 to 4, characterized in that: The following steps are involved: The acrylonitrile copolymer, the porogen and the good solvent are mixed and then formed into a film on a substrate to obtain the polyacrylonitrile ultrafiltration membrane.
6. The preparation method according to claim 5, characterized in that: The preparation method of the acrylonitrile copolymer is a water phase precipitation method; the water phase precipitation method comprises the following steps: mixing acrylonitrile monomer, unsaturated bond-containing monomer, initiator and water for free radical copolymerization.
7. The preparation method according to claim 6, characterized in that: The unsaturated bond-containing monomers include one or more of unsaturated acid monomers, unsaturated acid ester monomers, ammonium salts of unsaturated acids, and unsaturated amide monomers.
8. The preparation method according to claim 6 or 7, characterized in that: The temperature of the free radical copolymerization is 60-70° C., and the heat preservation polymerization time is 1-3 hours.
9. The preparation method according to claim 5 or 6, characterized in that: The mass ratio of the porogen to the good solvent is no more than 3:100; the mass ratio of the acrylonitrile copolymer to the good solvent is 1 to 10:
100.
10. Use of the polyacrylonitrile ultrafiltration membrane according to any one of claims 1 to 4 or the polyacrylonitrile ultrafiltration membrane obtained by the preparation method according to any one of claims 5 to 9 in water treatment.